Application of Ultrasonic Measurements for the Evaluation of Steel Fiber Reinforced Concrete - Gebretsadik, B.; Jadidi, K.; Farhangi, V.; Karakouzian, M. (Engineering, Technology & Applied Science Research, 2021)
This study investigates the feasibility of the application of ultrasonic measurement to characterize Steel-Fiber-Reinforced Concrete (SFRC). Specifically, the effects of steel fiber content, age, moisture content, and fiber orientation on Ultrasonic-Pulse-Velocity (UPV) were investigated. In this regard, beam and cylindrical samples were fabricated with different steel fiber contents. The result indicated that for beam specimens the UPV increases with the addition of fiber up to 2% and decreases for higher fiber percentages. Additionally, the fiber orientation within the beam specimens influences the UPV measurements. For cylindrical samples, the rate of UPV decreased with the addition of steel fiber reinforcement. In addition, it was discovered that the curing period affects the magnitude of UPV.